Litz wire RF coils for low frequency NMR applications. (November 2017) - Giovannetti, Giulio; Menichetti, Luca
Highlights: Radiofrequency coils are key components in Nuclear Magnetic Resonance systems. Litz wire conductor in the coil design can help to minimize coil losses. This paper reports the literature on Litz wires employed for coil design. Tests indicated Litz can be employed in MRI/particle hyperthermia systems. Abstract: Radiofrequency (RF) coils are key components in Nuclear Magnetic Resonance (NMR) systems since the use of dedicated coils is necessary for obtaining high-quality images. As a first approximation, an RF coil is essentially a tuned electrical circuit comprising an inductor and a capacitor. Conductors cross-geometry choice affects the coil overall performance, since the RF current doesn't flow uniformly in all the conductor volume. The use of Litz wire conductor for the RF coil design can help to maximize the surface where the current flows and to minimize the conductor resistance. This paper briefly reports the literature on Litz wires employed for MR coil design and their influence on coil performance. Successively four circular coils, tuned at frequencies in kHz and MHz ranges, were built by using wire and Litz wire conductors. Realized coils were tested and characterized by laboratory workbench in order to measure quality factors and to compare the performance of the different conductors typology. Our results are applicable in several situations as MR imaging in low field scanners, imaging of nuclear species at low fields, Overhauser systems and prepolarized NMR. Moreover, we believe Litz wire could be successfully employed in MRI/magnetic particle hyperthermia (MPH) systems.